Positioning Control Of An Ironless Linear Motor With Continuous Motion Nominal Characteristic Trajectory Following Controller - Foo,, Jia En (2017)
Ironless Permanent Magnet Linear Motors (IPMLM) are abundantly applied in various automated industries due to its capability of achieving high speed and high accuracy motions. Through the removal of transmission elements, the positioning performances of IPMLM are subjected by parameter changes and external disturbances, which is relatively difficult to model accurately. Besides that, since the IPMLM are often used in long working range applications, they are easily influenced by the saturation effect of the system, and may cause large overshoot. Therefore, in this research, a Continuous Motion-Nominal Characteristic Trajectory Following (CM-NCTF) controller is proposed for positioning control of an IPMLM. While the CM-NCTF controller was applied in various mechanism, the performance of CM-NCTF controller has yet to be validated for positioning control of IPMLM. The proposed controller consists of two components: A Nominal Characteristic Trajectory (NCT) and a proportional-plus-integral (PI) compensator. The NCT works as a motion reference for the IPMLM, where the PI compensator makes the system motion follows the constructed NCT. The NCT is constructed on a phase plane using the decelerating velocity of the IPMLM and its corresponding displacement in open loop configuration. This step enables the NCT to capture the nonlinearities of the IPMLM, without having to model the nonlinearities additionally. The PI compensator is designed using information from the NCT and open loop response of the IPMLM. A conditional freeze anti-windup is added to the PI compensator to eliminate actuator saturation effect, particularly due to the large integral gain, and due to large working range motion. The positioning performance in point-to-point and tracking motion is examined and compared to a Proximate Time Optimal Servomechanism (PTOS) controller experimentally. Experimental results show that the CM-NCTF controller does not exhibit any overshoot or steady state error at all, and has 370 % faster rise time than the PTOS controller at smaller displacement. In tracking motion, the CM-NCTF controller performs better than the PTOS controller, with at least 530 % improvement of tracking accuracy at small displacement, and 2400 % improvement of tracking accuracy at large displacement. In the evaluation of robustness against mass changes, experimental results and sensitivity analysis show that the CM-NCTF controller is robust towards mass variation as compared to the PTOS controller. In conclusion, the positioning performance of the CM-NCTF controller is validated on an IPMLM with high positioning and robust performance in the presence of mass variation as compared to PTOS controller, with no occurrence of actuator saturation problem.